Metal-catalyzed asymmetric hydrogenation : evolution and prospect - Dieguez, Montserrat; Pizzano, Antonio (Advances in catalysis, 2021)
Metal-Catalyzed Asymmetric Hydrogenation, Volume 68 in the Advances in Catalysis series, fills the gap between journal papers and textbooks across diverse areas of catalysis research. For more than 60 years, this series has recorded and presented the latest progress in the field of catalysis, giving the scientific community comprehensive and authoritative reviews. Chapters in this new release include Asymmetric hydrogenation of functionalized olefins, Asymmetric hydrogenation of unfunctionalized olefins or with poorly coordinative groups, Asymmetric hydrogenation of imines, Asymmetric hydrogenation of ketones, Asymmetric hydrogenation in industry, and Computational insights into metal-catalyzed asymmetric hydrogenation. This series is an invaluable and comprehensive resource for chemical engineers and chemists working in the field of catalysis in both academia and industry, with this release focusing on solid acids, surface acidity and heterogeneous acid catalysis.